Co z katechezą parafialną w Kościele w Polsce? - Misiaszek, Kazimierz (Studia Pastoralne, 2026)
Lack of parish religious education in Poland should be seen as a failure that is now bringing negative consequences. It is already a common belief, even among those who had originally been staunch advocates of the catechesis, that the so called religious education in schools has not brought the expected results. It has not become an effective element or means of development of faith among the younger generation of Poles. If it somehow manages to be successful it is to a negligible extent. Lack of religious education in parishes renders it impossible to fully form an adult, in particular while taking up and bringing into fruition the family catechesis. Furthermore, it goes without saying that young generations cannot be competently educated the Christian way without the input from their families. Understandably, adult catechesis will not become a panacea for the educational accomplishment of adults and children as well as the young people. Nevertheless, the presence of catechesis considerably increases the chances of more effective impact on education of children and young people alike. Only the parish catechesis is able to ensure the creation of the comprehensive and integral program of the development of Christian life.